MANAGERIAL ATTITUDES TOWARDS UNDERSTANDING THE EMPLOYEES’ NEEDS - Diskienė, Danuta; Drūteikienė, Greta; Marčinskas, Albinas (Ekonomika, 2012)
Abstract. The success of managing the activities of organizations is tightly related to solving the problem of effective work motivation. The solution is possible only by implementing an efficient employees’ motivation mechanism which is a considerable challenge to business organizations all over the world. The effectiveness of motivational tools created and used by managers is strongly correlated with recognizing the main needs of employees. Therefore, the authors of this paper tried to look at this important aspect of motivation through the prism of managerial attitudes. The empirical study was conducted in Lithuanian and Polish companies in which managers of different management levels took place. The purpose of the study has been to find out whether managers realize which needs are most important for their subordinates and whether they pay attention to these needs while pursuing an effective employee. The concept of this paper is based on the integration of management theory and actual practices.The methods of the study comprise system analysis, meta-analysis, survey, international comparisons. The findings of the study could be useful both for local companies’ managers and for foreign companies deciding to enter the Eastern Europe an market as well for researchers interested in CEE countries’ management peculiarities.Key words: employees’ needs, motivation, motivational profile, managerial attitudes